Análise de eventos de precipitação extrema na costa leste do nordeste brasileiro utilizando conexão de imagens de satélites e de radar meteorológico - Santos, José André Silva dos (2012)
Due to the current needs with regard to studies of extreme weather events, the main aim of this work was to initiate a project to create a precursor product able to assist in real-time analysis of extreme events using radar and satellites. Analysis of intense rainfall recorded in the East Coast of Northeast Brazil (ENE) in the region from 17 to 19 June 2010 were held, located in the basins of Mundaú and Paraíba, Alagoas rivers cities, obtained from the ESRL website / PSD / NOAA. Besides the rainfall analyzes satellite images and weather radar were used. The condition of severe weather and flooding was recorded a tropical storm subsynoptic scale, due to the intense convergence of the flow of moisture from the Atlantic. These rains, particularly of the day June 18, 2010, fell on the states of Pernambuco, Capibaribe River basin, and in the basins of MundaúAlagoas and Paraíba rivers and caused floods, deaths, property damage and other disorders to society location. The product created is able to identify which are precipitating clouds, through the connection of radar and satellites, reducing the errors that are made when rainfall estimates through solely from satellite images.